Analisis Quality of Service pada Implementasi Video Call Berbasis SIP dengan Monitoring Zabbix pada Jaringan WLAN - Avrian, Daniel Okta; Lase, Kristian Juri Damai; Maedjaja, Febe (Progresif: Jurnal Ilmiah Komputer, 2026)
The development of IP-based communication technology has made video call services an efficient solution for real-time communication. This study analyzes the Quality of Service (QoS) performance of SIP-based video call implementation using the Zabbix monitoring system on a Wireless Local Area Network (WLAN). An experimental method was applied by implementing an Issabel PBX SIP server and conducting performance tests under five bandwidth variations, namely 2.5, 5, 10, 15, and 20 Mbps. Each test scenario was conducted for 15 minutes with a monitoring interval of 30 seconds. The evaluated QoS parameters include throughput, delay, jitter, and packet loss, which were assessed based on the TIPHON standard. The results show that higher bandwidth provides better QoS performance, while bandwidth limitation leads to performance degradation, particularly in packet loss and service stability. The evaluation also indicates that a minimum bandwidth of 5 Mbps is required to maintain acceptable video call quality on WLAN networks. Furthermore, this study demonstrates that Zabbix is effective as a continuous monitoring system capable of providing real-time and historical QoS data to support performance analysis and network evaluation.Kata kunci: Quality of Service; Session Initiation Protocol; Video call; Zabbix; WLAN.